Welcome to Brazil: An Analysis of the Migration of Foreign Players to Brazilian Basketball - Jeferson Roberto Rojo; Joao Paulo Melleiro Malagutti; Felipe Canan; Edson Hirata; Fernando Augusto Starepravo (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2021)
This study aimed to analyze the migration of foreign athletes to compete in the New Basketball Brazil (NBB). This descriptive study was used for documentary research, and data were collected from the National Basketball League (LNB), referring to all seasons of the competition. The results point to a gradual increase in the number of foreign players until the 2013/14 season, after a slight decline. It was also observed that Minas was the club that received the most foreigners and that counted on them in all the seasons. The country with the highest number of migrant athletes in the NBB was the United States. It was concluded that the pattern of migration of foreigners in Brazilian basketball is predominantly continental and that the coming of many Americans to Brazil can be explained by the fact that the United States is the mother country of many players whose quality is superior to their domestic demand. That leads these players to leave the world's largest basketball league, the NBA, corroborating the reality of other countries' leagues around the world.